KOMUNITAS IKAN KARANG DI PANTAI SAWANGAN DAN KUTUH, BALI - I Wayan Arthana (Environmental Research Center (PPLH) of Udayana University, 2009)
The research has been done at Sawangan coastal water (S 08o49’44,7” E 115o13’20,3”) and at Kutuh coastal water (S 08o50’46,8” E 115o12’07,9”) using manta tow survey and line intercept transect (LIT) at the depth of 9-10 m. At Sawangan it was observed 12 family with 16 species of coral fishes. Family of Lambridae had the bigest individual number (19 individual) which came from species of Cleaner Wrasse (Labroides dimidiatus) with 17 individual and Moon Wrasse (Thalassoma lunare) with 2 individual. At Kutuh it was observed 10 family with 15 species of coral fishes. Family of Pomacentridae and Chaetodontidae had the bigest individual number which came from species of Paletail Chromis (Chromis xanthura ) and Indian Vagabond Butterflyfish (Chaetodon decussatus) with 4 individual each. In total, at Sawangan and Kutuh it was observed 13 family of coral fishes. Among those 13 family, coral fish community from family of Caesionidae, Cirrhitidae and Diodontidae were not available at Kutuh, moreover coral fish from family of Pempheridae was not available at Sawangan. As an ecosystem, the condition of coral fishes at Kutuh were more stable compared to that at Sawangan in which at Kutuh, the diversity index value was bigger and dominant index value was smaller.